2019
DOI: 10.1186/s12909-019-1791-8
|View full text |Cite
|
Sign up to set email alerts
|

High enthusiasm about long lasting mentoring relationships and older mentors

Abstract: Background Mentoring plays a pivotal role in workplace-based learning, especially in the medical realm. Organising a formal mentoring programme can be labor and time intensive and generally impractical in resource constrained medical schools with limited numbers of mentors. Hence, informal mentoring offers a valuable alternative, but will be more likely to be effective when mentors and protégés share similar views. It is therefore important to gain more insight into factors influencing percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…This power imbalance was described by supervisors as affecting the supervisortrainee relationship negatively. Clarity of the power differential, transparency in the hierarchy, and trust between supervisor and trainee are key (Castanelli et al, 2022;Falender & Shafranske, 2017;Mohtady et al, 2019). The power imbalance requires further attention in the community pharmacy specialization program and also in other programs with a similar structure.…”
Section: Conflicting Roles Of the Supervisormentioning
confidence: 99%
“…This power imbalance was described by supervisors as affecting the supervisortrainee relationship negatively. Clarity of the power differential, transparency in the hierarchy, and trust between supervisor and trainee are key (Castanelli et al, 2022;Falender & Shafranske, 2017;Mohtady et al, 2019). The power imbalance requires further attention in the community pharmacy specialization program and also in other programs with a similar structure.…”
Section: Conflicting Roles Of the Supervisormentioning
confidence: 99%
“…x Selection of excellent host mentors in excellent institutions: We pay attention to the track record of host mentors and their reputation [5]. Learning from 'big shots' [3,6], in direct contact, motivates and improves the chances for conducting excellent research and achieving excellent publications. x Alumni network: A network of alumni that are willing to support young academics in finding attractive research projects and locations is another very important asset, which has frequently been mentioned by our students.…”
Section: Success Factors and Scholarship Students' Feedbackmentioning
confidence: 99%
“…Successful mentorship, on the other hand, is characterized by dedication and motivation, good communication, clear definition and mutual understanding of goals [2]. In particular, mentoring by experienced, top clinicians and clinical scientists is regarded as especially beneficial [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research found that systems-thinking, strategic, anticipatory, normative and interpersonal, effective mentor, able to spend time with, communicate or respond effectively to the student, ability to encourage, high level of professional skills, pedagogy skills, disciplined, supportive, motivating and ability to lead others, ability to convey constructive and thoughtful criticism in a patient and sensitive manner would help to foster student competencies and skills in the TVET field (Prunuske et al, 2019;Mohtady et al, 2019); Herlandy, 2019). It is advocated that TVET must be designed and monitored by someone who understands about the working process in the company and the things students need to learn during the internship (McGee, 2017;Moses, 2016).…”
Section: Background Of the Studymentioning
confidence: 99%